Opposition effects of Jupiter's satellites Io and Europa - Shavlovskij, V.I. (Кинематика и физика небесных тел, 2005)
Using long-term photoelectric observations of Io by Shavlovskij and Europa by Thompson et al. [10] at solar phase angles from 0° to 12° we determined solar phase functions for the leading and trailing hemispheres of the satellites. The obtained values of the half-width at half-maximum (HWHM) of the opposition peak prove that the opposition effects of Io and Europa are caused by coherent backscattering.